Storage of pollen and properties of olive stigma for breeding purposes - Zambon, Carolina; Silva, Luiz Fernando; Pio, Rafael; Bianchini, Flávio; de Oliveira, Adelson (Revista Ciência Agronômica, 2018)
In order to ensure success in controlled hybridizations in olive tree cultivation, the information on pollen viability and stigma receptivity is essential. The aim was to establish methodologies that increase the preservation of pollen viability and to establish the time to perform crossbreeds in hybridization studies with olive trees. Three experiments were performed with plants from the cultivar Arbequina, in Maria da Fé, MG, Brazil. In the first experiment, the description of the flower events was performed. In the second, anthers were desiccated in eppendorfs, being stored at three different conditions for pollen viability test: room temperature (27 °C), refrigerator (8 °C) and freezer (-10 °C). In order to evaluate the in vitro germination, culture medium for olive pollen grains was used. In this respect, pollen grains were transferred in Petri dish containing culture medium and placed in a BOD (biochemical oxygen demand) chamber at 28 °C for 60 h, being counted. The first evaluation was performed prior to the assembly of the experiment, testing the initial viability, whereas the second occurred 24 h after storage. Subsequently, seven evaluations were performed fortnightly. In the third experiment, the stigma receptivity was verified by the 3% hydrogen peroxide method, with flowers in pre-anthesis, anthesis and post-anthesis, evaluated hourly in the period from 7 a.m. to 6 p.m. for three days. In the description of the flower events, it was verified that the olive tree shows diurnal anthesis, with flower opening between 10 a.m. and 11 a.m. The anthers stored in a freezer preserved the viability for 60 days and the stigmas were receptive since the pre-anthesis.